PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan CV. Sri Rasa Kota Bengkulu) - Anggi Risnawati; Barin Barlian; Arga Sutrisna (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
This study aims to examine and analyze the effect of compensation and work discipline on the performance of employees of CV. Sri Rasa. Respondents in this study were employees of CV. Sri Rasa. Based on the sample method, the total sample in the study was 37 respondents. In this study using primary data obtained from the distribution of questionnaires. The number of questionnaires distributed was 37 copies and which could be returned and processed were 37 copies. The analytical method used in this research is multiple linear analysis. The results showed that compensation had no a significant effect on employee performance, work discipline had a significant effect on employee performance and compensation and work discipline simultaneously had a positive and significant effect on employee performance. This means that when compensation and work discipline are high, employee performance increases.